Lands Cover Dynamics of Siais Lake Catchment Area, Tapanuli Selatan District, Indonesia. Issue 1 (1st December 2022) - Samsuri; Zaitunah, A; Ahmad, AG; Pasaribu, I
Abstract: The Siais Lake Catchment Area (SLCA) is a water resource that includes various types of land cover and land use in Rianiate village, Angkola Sangkunur sub-district, and Tapanuli Selatan district. The SLCA lake catchment area has altered the land cover and increased the surface area of Siais Lake. The purpose of this study was to determine the type of land cover that changed in the Siais lake catchment area between 1990 and 2018. The land cover classification was obtained using Landsat 5 and Landsat 8 OLI images. Make use of supervised classification. Forest, plantation, bare land, paddy field, settlement, waterbody, shrub, and swamp were the land covers identified in the Lake Siais catchment area. Plantations had the highest percentage of land cover increase from 1990 to 2018, with an increase of 3, 995.87%, while paddy fields had the highest decrease, with a decrease of 93.77%. .